District Census Handbook, Shimoga, Part XIII-A & B, Series-9 - Das, B.K. (Karnataka, 1981)
Village and Town Directory, Town Directory, Status and Growth History, Physical Aspects and Location of Towns, Municipal Finance, Civic and Other Amenities, Medical, Educational Recreational Facilities
Keywords: Village and town Directory; Village and townwise Primary Census Abstract